The Aging Warriors: A Study on the Retiring Oil and Gas Professionals - Sheikh Annuar, Sh A Rahim; Farha, Mohd (2021)
International Oil and Gas organizations face the gruelling task of juggling the right talent for the job, or risk cost over-run due to inefficient talent management while executing multiple projects simultaneously. The cost, time and quality of the project are governed by evolving demand and supply in this industry. There is a shift in the current approach in resource management to cushion the ageing workforce constraints in the Oil and Gas industry. It is a fact that the crucial knowledge is diluted as these seniors leave the industry without proper handover and documented lessons learned. This study was conducted in a Malaysian Oil and Gas company context. The rich meaning was extracted from semi-structured interviews, which derived the key causes of skill shortage in Oil and Gas. The objective was to find a governance matrix easily adaptable for senior expert workers and retirees in a postCOVID environment. Qualitative findings highlight five key elements in effective knowledge downloading; namely experience, knowledge, manpower, tools and skills. This is intertwined with the issue of an ageing workforce. This paper will deliberatechallenges faced in project management and suggests the best method in adapting the ageing workforce dilemma. Findings in the study indicate that there is an equal correlation of the gaps studied in producing optimal results; with the strong importance of optimizing experiences of the senior workforce. Project management systems demand continuity as the old is replaced with the new generational workers. The catalyst to dynamic resource management is governance; it reflects increased efficiency in the organization as a whole. The interpretations and conclusions are suited for Oil and Gas skill group enhancement, but generalized to suit other knowledge-dependent industries.